Microbiological, Epidemiological, and Clinical Characteristics of Patients With Cryptococcal Meningitis at a Tertiary Hospital in China: A 6-Year Retrospective Analysis - Li, Yanbing; Zou, Mingxiang; Yin, Jun; Liu, Ziqing; Lu, Binghuai (Frontiers in Microbiology, 2020)
Cryptococcal meningitis, mainly caused by Cryptococcus neoformans/gattii species complexes, a lethal infection in both immunosuppressive and immunocompetent populations. We characterized 110 Cryptococcus strains collected at Xiangya Hospital of Central South University in China during the 6-year study period between 2013 and 2018, and antifungal susceptibility testing was also performed. Furthermore, the clinical features, laboratory and imaging data, treatment strategies and outcomes of the subjects were retrospectively analyzed. Of 110 Cryptococcus strains, C. neoformans species complexes (VNI and VNIV genotype) accounted for 95.5% (105/110) and 0.9% (1/110), respectively, and 4 were Cryptococcus deuterogattii (VGII genotype) (3.6%). The strains were further classified into 17 individual sequence types (STs) by using multilocus sequence typing (MLST), and 89.1 % (98/110) were represented by ST5. All 4 C. deuterogattii strains were assigned as ST7 and 1 Cryptococcus deneoformans strain was assigned as ST260. Antifungal minimal inhibition concentrations higher than the epidemiologic cutoff values (ECVs) were found mainly in C. neoformans species complexes strains (9 for amphotericin B, 9 for fluconazole and 7 for 5-fluorocytosine). Furthermore, in the subjects, 60.9% (67/110) were male; liver diseases (hepatitis/HBV carrier and cirrhosis) were the most common underlying conditions (11.8%, 13/110), followed by autoimmune disorders (10.9%, 12/110) and chronic kidney disease (6.36%, 7/110); only 4.5% (5/110) were HIV/AIDS; 40.0% (44/110) did not have underlying diseases. For clinical presentation, headache (77.3%, 85/110), fever (47.3%, 52/110), and stiff neck (40.9%, 45/110) were commonly observed. The mortality rate was 35.0% (36/103). In conclusion, our data were characterized by a high prevalence of the patients without HIV/AIDS and other underlying status, a relatively high non-wild-type rate to fluconazole and amphotericin B, and low genetic diversity in C. neoformans species complexes strains. The present study will provide evidence for further improvement of the diagnosis and treatment of the disease in China.